Sexual orientation and gender identity data: An observational study assessing the feasibility of SOGI collection in clinical research and patient assistance programs - Isabel Brown; Thuan Tran; Audrey Funwie; Shilpen Patel; Keith Dawson; Meghan McKenzie (PLoS ONE, 2025)
Purpose Sexual and gender minority (SGM) people often experience significant health disparities and poor health outcomes. The objective of this study was to assess the feasibility and outcomes of sexual orientation and gender identity (SOGI) data collection in 2 distinct survey settings: (1) clinical research and (2) patient assistance programs. Materials and methods In this survey study, participants completed 1 of 2 separate, distinct, self-reported, optional, United States–based surveys: (1) an in-person survey at clinical research sites for a cough or cardiac study between December 2022 to December 2023 (sponsored by Genentech) or (2) a web-based patient assistance program survey from a patient assistance program between January 2023 to December 2023 (sponsored by the Genentech Patient Foundation). Results Of 33 clinical research survey participants, 100% of participants answered SOGI-related questions, leading to a non-response rate of 0%. Most (87.88%) participants identified as cisgender; 84.85% identified as heterosexual, 3.03% bisexual, 3.03% gay, 3.03% questioning, and 6.06% preferred not to answer. Of 8499 patient assistance program survey participants, 99.54% answered gender identity questions (non-response rate of 0.46%) and 95.92% answered sexual orientation questions (non-response rate of 4.08%). Gender identities in the patient assistance program survey included 61.30% female, 34.22% male, 0.12% genderqueer, 0.06% transgender male, 0.14% none of the options, and 4.16% “Prefer not to answer.” Self-reported non-heterosexual orientations included bisexual, gay, lesbian, queer, questioning, “Prefer not to answer,” and something else. Conclusions These findings suggest that patients in both survey settings are willing to self-disclose sexual orientation and gender identity information. These results underscore the rationale for adopting SOGI data collection in these settings. Clinical trials NCT05660850, ISRCTN10520571